The Utilisation of Persea Americana Seed Oil for Solvent-Based Paint Application - Fasina, Esther; Lawal, Nurudeen Muhammad; Aisuedion, Martins Ehimare; Mustapha, Aisha Grema; Azeez, Kabiru Oyetunde; Uhiene , Titus; Gidigbi, Joshua (PUI BiGME Universitas Jambi, 2026)
The need for industrial sustainability necessitates the development of bio-based feedstock. The persea americana seed was prepared and oil was subsequently extracted using Soxhlet extractor. The result of the physicochemical properties conformed with the literature. Further alcoholysis-modified alkyd process was carried out on the persea americana seed oil (PASO) to form persea americana seed oil modified alkyd resin (PASOM). The FTIR analysis of the PASOM revealed crucial peaks associated with alkyd resin. This shows that the novel PASOM resin was successfully synthesized. The PASOM resin also shows better resistance with chemical attacks. The characterisation of the solvent-based paint producing using PASOM resin conforms with the standard and shows better performance with chemical media. The PASOM exhibit better performance with adhesion, thereby reduces paint peeling when used.